2014
DOI: 10.30638/eemj.2014.208
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Technological and Natech Risk for Two Petroleum Product Tanks Located in Seismic Area

Abstract: The failure of process equipment due to the impact of natural hazards, the so-called Natech events, have generated several industrial accidents, such as Fukushima, Japan -2011, Ichihara, Japan -2011, Tupras, Turkey -1999, Northridge, US -1994, causing the release of large quantities of hazardous materials in the environment. Earthquakes occupy a leading position in the list of natural hazards with Natech potential, causing serious damage and the loss of containment in process equipment. The present study revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, the comparison of individual risk (IR) and social risk (SR) accident assessment modeling on two tanks containing flammable hydrocarbons using ARIPAR-GIS software has indicated an increase in the individual risk (IR) and social risk (SR) in the Natech events scenario caused by a high MW earthquake compared with the technological accident scenario [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the comparison of individual risk (IR) and social risk (SR) accident assessment modeling on two tanks containing flammable hydrocarbons using ARIPAR-GIS software has indicated an increase in the individual risk (IR) and social risk (SR) in the Natech events scenario caused by a high MW earthquake compared with the technological accident scenario [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated earthquakes have more severe scenarios than other natural hazards due to damaging simultaneously a large number of industrial equipment [ 10 ]. Examining the documents and seismic records of the Tehran south Faults have shown the experience of a large number of powerful and destructive earthquakes (moment magnitudes of 7.1, 7.2, and 7.6 on the Richter scale) in the Ray region, each of which was accompanied by human heavy casualties [ [19] , [20] , [21] , [22] , [23] ]. Tehran is one of the 20 metropolises of the world and one of the 17 metropolises with a resident population of over 10 million people and a floating population of 4 million people [ 24 ], which is located in an area with a very high relative risk of earthquakes [ 18 , 19 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Landucci et al (2017) studied QRA in the field of hazardous materials transportation, focusing on the analysis of current procedures and tools as well as on the different methodologies available. Krausmann et al (2011) and Gheorghiu et al (2014) studied QRA for the assessment or the risks related to another type of threat for Seveso sites, that is, threats deriving from natural agents (a.k.a. Natech events); the former provided a nine steps-based innovative approach framed into QRA, whereas the latter compared the Individual Risk and Societal Risk achieved between conventional technological risk and Natech risk, focusing on specific events such as an earthquake for two petroleum product tanks.…”
Section: Risk Assessment Methods For Seveso Sitesmentioning
confidence: 99%